Effects of Dietary Levels of Methionine on Broiler Performance and Carcass Characteristics - Ahmed, Mohamed Elamin; Abbas, Talha E. (International Journal of Poultry Science, 2011)
The present experiment was carried out to determine the effect of dietary methionine levels higher than NRC recommendation on broiler performance and carcass traits. Four dietary levels of methionine 0, 100, 120 and 130% of NRC recommendation were used. Dietary levels of methionine, expressed as percentage of NRC recommendations, significantly (p<0.05) affected feed intake, Feed Conversion Ratio (FCR) and Protein Efficiency Ratio (PER). Feed intake was numerically improved with 110 and 130% of NRC methionine, but was not improved by 120% NRC methionine. Body weight gain was significantly (p<0.05) improved by 110 and 130% of NRC methionine compared to the control. The broiler chicks on methionine higher than NRC showed significant (p<0.05) increase in absolute and relative weight of breast and significant (p<0.05) decrease in abdominal fat.